2021
DOI: 10.30871/jama.v5i1.2738
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spin-Off Policy and Macroeconomic Fundamental Factors on Third Party Funds at Sharia General Banks

Abstract: In enhancing the development of Islamic banking, the government issued Law No. 21 of 2008 concerning spin-off. With this policy, it is expected that Islamic Commercial Banks will develop. This study aims to implement panel data regression to examine in depth the influence of spin-off policy and macroeconomic fundamental factors on third party funds of Sharia General Banks. Sampling by purposive sampling, six (6) Sharia General Banks that have conducted spin-offs and financial report data from 2014-2018. The Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Research has also found that conversion strategies yield better results, particularly for profitability and efficiency than pure spin-off strategies. Alkaf and Nawasiah (2021) conducted research by purposive sampling, on six (6) BUS that had carried out spin-offs and financial report data for 2014-2018. Empirical results show that the spin-off policy and macroeconomic fundamentals had a significant effect on third-party bank funds simultaneously.…”
Section: Previous Study-spin Offmentioning
confidence: 99%
“…Research has also found that conversion strategies yield better results, particularly for profitability and efficiency than pure spin-off strategies. Alkaf and Nawasiah (2021) conducted research by purposive sampling, on six (6) BUS that had carried out spin-offs and financial report data for 2014-2018. Empirical results show that the spin-off policy and macroeconomic fundamentals had a significant effect on third-party bank funds simultaneously.…”
Section: Previous Study-spin Offmentioning
confidence: 99%